1979
DOI: 10.1007/bf00429693
|View full text |Cite
|
Sign up to set email alerts
|

Lithium administration antagonizes cholinergic behavioral effects in rodents

Abstract: Physostigmine, a centrally acting cholinesterase inhibitor, antagonizes methylphenidate-induced stereotyped gnawing behavior in mice and rats. This effect is significantly attenuated when lithium chloride is concurrently administered, indicating that lithium chloride may antagonize central cholinergic activity. This observation may have theoretical implications for an adrenergic-cholinergic balance hypothesis of affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Thus, neuronal systems exposed to intense stimulation are likely to react preferentially with reduced responsiveness under lithium treatment. The finding that repeated lithium treatment reduced the antagonism by physostigmine of methylphenidateinduced stereotypies (Janowsky et al, 1979b) may represent a behavioral correlate of this with respect to the cholinergic system. The interaction of lithium with phosphoinositol metabolism could be a basis of Dilsaver's idea of stabilization of cholinergic transmission.…”
Section: Interactions With Cholinergic Transmissionmentioning
confidence: 98%
“…Thus, neuronal systems exposed to intense stimulation are likely to react preferentially with reduced responsiveness under lithium treatment. The finding that repeated lithium treatment reduced the antagonism by physostigmine of methylphenidateinduced stereotypies (Janowsky et al, 1979b) may represent a behavioral correlate of this with respect to the cholinergic system. The interaction of lithium with phosphoinositol metabolism could be a basis of Dilsaver's idea of stabilization of cholinergic transmission.…”
Section: Interactions With Cholinergic Transmissionmentioning
confidence: 98%
“…It is noteworthy that this report comes from the San Diego group of Janowsky, Judd, and colleagues. This group has also reported that lithium antagonizes behavioral effects of cholinergic agents in rodents (Janowsky et al 1978(Janowsky et al , 1979(Janowsky et al , 1982. Hence, the same group reports data capable of supporting contradictory viewpoints.…”
Section: Responsementioning
confidence: 98%
“…Tricyclics also cause rapid cycling in bipolar patients (Wehr and Goodwin 1979). In contrast, treatments down-regulating or subsensitizing cholinergic systems, e.g., seizures (Byrne et al 1980;Dashieff and McNamara 1980;Dashieff et al 1981Dashieff et al , 1982, and lithium (Janowsky et al 1979;Levy et al 1982; often abort rapid cycling. recently reviewed the effects of tricyclics, lithium, and electroshock (EST) on cholinergic mechanisms and suggested that the hypotheses "up-regulation or supersensitivity of cholinergic systems is involved in the induction of tricyclic associated rapid-cycling" and "the probability of a bipolar patient who has never exhibited rapid-cycling, developing a rapid-cycling course is a function of an enhanced propensity of critical central cholinergic systems to become supersensitive in response to endogenous or exogenous (e.g., tricyclic treatment) assaults many of us are subjected to without ill effect" are heuristically important.…”
Section: Introductionmentioning
confidence: 99%